1994
DOI: 10.1063/1.356348
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Raman spectrum of nanometer SnO2

Abstract: The Raman spectra of nanometer-sized particles of SnO2 (3–90 nm) at room temperature are reported. In the Raman spectra of the particles of SnO2, which are quite different from that of single-crystal SnO2, there appear two new characteristic peaks, and their intensities decrease gradually with the increase of crystal size. It is concluded that the new peaks can be explained by the surface phonon modes of nanometer SnO2, consequently there is a relation between the structures of surface layers and bulk. It is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(88 citation statements)
references
References 7 publications
12
75
0
1
Order By: Relevance
“…34 Despite the number of publications related to SnO 2 and Raman spectroscopy, however, they have not generally been reported for SnO 2 . [12][13][14][15] An exception to this is our previous paper 11 in which we demonstrated them to be an effective way of evaluating not only the average nanoparticle size, but also the whole size distribution.…”
Section: Low Frequency Modes Of Sno 2 Nanoparticlesmentioning
confidence: 82%
See 2 more Smart Citations
“…34 Despite the number of publications related to SnO 2 and Raman spectroscopy, however, they have not generally been reported for SnO 2 . [12][13][14][15] An exception to this is our previous paper 11 in which we demonstrated them to be an effective way of evaluating not only the average nanoparticle size, but also the whole size distribution.…”
Section: Low Frequency Modes Of Sno 2 Nanoparticlesmentioning
confidence: 82%
“…Low frequency bands have been observed previously in SnO 2 , 11 and several authors have reported the existence of bands not observed in single-crystal or polycrystalline SnO 2 which have been found to be closely related to grain size. [12][13][14][15] However, some of these reports do not adequately explain the origin of the abnormal spectrum.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…are not observed for bulk SnO 2 might be due to the shape of the SnO 2 nanostructure [39] because it will affect the surface phonon modes. [40] In fact, a diffused peak at ∼622 cm −1 has been reported for nanocrystalline SnO 2 material [41] present on the surface of ancient Chinese black mirrors. It is well known that in an infinitely perfect crystal only the phonons near the center of the BZ contribute to the scattering of incident radiation because of the momentum conservation rule between phonons and incident light.…”
Section: Resultsmentioning
confidence: 98%
“…Tin dioxide in the rutile form belongs to the symmetry space group D 4h [21][22][23][24][25][26] . The 6 units cell atoms give rise to 18 vibrational modes.…”
Section: Resultsmentioning
confidence: 99%